Cognitive behaviour therapy with compulsive hoarding: a single case study - Aasma Yousaf; Rukhsana Kausar; Iram Fatima (Journal of the Pakistan Medical Association, 2020)
The current case study used cognitive behaviour treatment (CBT) for the management of a 35-year-old, married man who presented with complaint of compulsive hoarding. The complaint of compulsive hoarding (excessive acquisition, difficulty in discarding saved material and cluttering) was accompanied by feeling of anger, sad mood, low confidence, decreased sleep and appetite, poor problem solving ability, indecisiveness and interpersonal conflicts. The study was approved by the institutional research committee (Departmental Doctoral Programme Committee) and followed by the university research committee (Advance Studies and Review Board) as academic requirement for the duration of 2013-2020. Written consent was also taken from the individual to publish the results of the case. Twenty-eight CBT sessions of one-hour duration were conducted, over a period of six months. Continuous...